The scientific revolution : A brief history with documents - Jacob, Margaret C. (The bedford series in history and culture, 2010)
Exploring the Scientific Revolution from its origins in the early sixteenth century to its widespread acceptance in Western societies in the late eighteenth century, Scientific Revolution argues that the revival of ancient texts in the Renaissance and the upheaval of the Protestant Reformation paved the way for science.